Robust Data Partitioning. - Jindal, Alekh; Shanbhag, Anil; Lu, Yi (Encyclopedia of Big Data Technologies, 2018)
This chapter described new advancements in data partitioning for modern applications that are ad-hoc in nature and do not have any upfront query workload.